(untitled) (SCHOOLAR: Social and Literature Study in Education, 2022)
This research is based on the intellectual intelligence possessed by students. students are seen as someone who has a good personality because in the boarding school many things are taught, including discipline, craft, decency, cleanliness, order, and others. The students’ awareness has not been fully reflected in the students of the Hasbullah Islamic Boarding School. The purpose of this study was to determine the level of intellectual intelligence and awareness of students in carrying out the rules at the Hasbullah Islamic Boarding School, as well as to analyze whether or not there was a relationship between the level of intellectual intelligence and the awareness of students at the Islamic boarding school. The approach used in this study is a quantitative approach. Collecting data using observation, questionnaires, interviews, and documentation. For research data analysis, researchers used product moment correlation analysis to obtain results from the established hypothesis. The research shows that the students’ intellectual intelligence has high criteria, students’ awareness in implementing the rules is high criteria, and r count is 0.425 greater than r table, so that Ha is accepted, namely "There is a relationship between the level of intellectual intelligence with students’ awareness in carrying out the regulations of the Islamic Boarding School Hasbullah Bahrul â€˜Ulum Tambakberas Jombang".